Oxford Shakespeare : Henry IV, Part 2. - Shakespeare, William (Oxford University Press, 1998)
This edition offers a modernised text of the second part of 'Henry IV'. It also argues that the character of Falstaff was originally called Oldcastle in both parts, and that the Folio-only passages in the play reflect the text of the original prompt-book.